Extra-nodal metastasis should be classified separately from lymph node metastasis in gastric cancer. Issue 5 (May 2021) - Nishiwaki, Noriyuki; Irino, Tomoyuki; Fujiya, Keiichi; Kamiya, Satoshi; Hikage, Makoto; Tanizawa, Yutaka; Bando, Etsuro; Kusafuka, Kimihide; Terashima, Masanori
Abstract: Introduction: Extra-nodal metastasis (ENM) is defined as a tumor nodule without histological evidence of a lymph node structure. Although ENM has pathological features distinct from those of metastatic lymph nodes, both ENM and metastatic lymph nodes are considered within the same category in the pathological nodal (pN) classification. This study aimed to clarify the clinicopathological characteristics and prognostic relevance of ENM in gastric cancer patients who underwent curative gastrectomy. Materials and methods: We retrospectively evaluated 1207 Japanese patients who underwent curative gastrectomy at a single center between January 2009 and December 2013. All resected specimens were fixed in 10% formalin, processed, and stained using hematoxylin and eosin, and subsequently reviewed by two pathologists. Survival times were analyzed using the Kaplan-Meier method, and independent prognostic factors were identified using a Cox proportional hazards regression model. Results: Patients who were ENM-positive had significantly poorer overall survival; multivariable analysis revealed that independent prognostic factors were older age (hazard ratio [HR]: 3.68, 95% confidence interval [CI]: 2.60–5.20), higher pathological tumor classification (HR: 2.28, 95% CI: 1.43–3.62), presence of metastatic lymph nodes (HR: 1.57, 95% CI: 1.0–2.36), and ENM-positive status (HR: 2.33, 95% CI: 1.48–3.66). ENM-positive patients had similar survival outcomes to those of ENM-negative patients with ≥16 metastatic lymph nodes. Conclusions: Among Japanese patients with gastric cancer who underwent curative gastrectomy, ENM was an independent prognostic factor with a prognostic significance different from that of lymph node metastasis. These results suggest that ENM and lymph node metastasis should be classified separately.